2021
DOI: 10.1111/jerd.12863
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of in‐office dental bleaching with and without sonic activation: A randomized, split‐mouth, double‐blind clinical trial

Abstract: Objective: This study was aimed at comparing the bleaching efficacy and bleaching sensitivity (BS) of two higher-concentration in-office bleaching gels (37% carbamide peroxide [CP] and 38% hydrogen peroxide [HP]) applied under two conditions: alone or in association with sonic activation.Methods: Fifty-six volunteers were randomly assigned in the split-mouth design into the following groups: CP, CP with sonic activation (CPS), HP, and HP with sonic activation (HPS). Two in-office bleaching sessions were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The following types of light are the most frequently used: LED, plasma arc and halogen. From a chemical viewpoint, this irradiation should not change the oxidative effect of hydrogen peroxide, but it may enhance the reaction rate due to local temperature increases [41][42][43][44][45][46].…”
Section: In-office Treatmentsmentioning
confidence: 99%
“…The following types of light are the most frequently used: LED, plasma arc and halogen. From a chemical viewpoint, this irradiation should not change the oxidative effect of hydrogen peroxide, but it may enhance the reaction rate due to local temperature increases [41][42][43][44][45][46].…”
Section: In-office Treatmentsmentioning
confidence: 99%
“…Prior studies demonstrated the potential of 37% carbamide peroxide, roughly equivalent to 12% hydrogen peroxide, in minimizing post‐bleaching sensitivity [10, 11]. Nevertheless, it is essential to recognize that the efficacy of 37% carbamide peroxide for in‐office bleaching has been investigated to a lesser extent, and the studies have consistently indicated a somewhat diminished bleaching impact compared to high‐concentration hydrogen peroxide agents [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of tooth bleaching is not fully understood, but the bleaching effect seems to be achieved by increasing the opacity of the enamel and oxidizing phosphoproteins in the dentin, which are responsible for tooth discoloration [1,2]. In-office tooth bleaching is a common Prior studies demonstrated the potential of 37% carbamide peroxide, roughly equivalent to 12% hydrogen peroxide, in minimizing post-bleaching sensitivity [10,11]. Nevertheless, it is essential to recognize that the efficacy of 37% carbamide peroxide for in-office bleaching has been investigated to a lesser extent, and the studies have consistently indicated a somewhat diminished bleaching impact compared to highconcentration hydrogen peroxide agents [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation